Die Inschriften zu den Ludi saeculares. Acta ludorum saecularium - Schnegg, Bärbel (De Gruyter, 2020)
The Saecular Games are considered one of the best-testified religious festivals of ancient Rome. The most significant source are two inscriptions, the Acta augustea and the - partially badly damaged - Acta severiana. The volume offers a completely newly constituted Latin text of both inscriptions with translation and detailed commentary. In addition, other important texts to the Ludi saeculares are provided in the original and in translation.
German
Keywords: Ludi saeculares; Ancient Rome; inscriptions